Transcranial direct current stimulation for Obsessive-Compulsive Disorder: patient selection and perspectives - da Silva RMF; Brunoni AR; Miguel EC; Shavitt RG (Neuropsychiatric Disease and Treatment, 2019)
Renata de Melo Felipe da Silva,1 Andre Russowsky Brunoni,2 Eurípedes Constantino Miguel,1 Roseli Gedanke Shavitt3 1Department and Institute of Psychiatry, Obsessive-Compulsive Spectrum Disorders Program and Service of Interdisciplinary Neuromodulation (SIN), Hospital das Clinicas HCFMUSP, Faculdade de Medicina, Universidade de Sao Paulo, Sao Paulo, SP, Brazil; 2Department and Institute of Psychiatry, Department of Internal Medicine, Laboratory of Neurosciences (LIM-27), Service of Interdisciplinary Neuromodulation (SIN), Hospital das Clinicas HCFMUSP, Faculdade de Medicina, Universidade de Sao Paulo, Sao Paulo, SP, Brazil; 3Department and Institute of Psychiatry and Director of the Obsessive-Compulsive Spectrum Disorders Program, Hospital das Clinicas HCFMUSP, Faculdade de Medicina, Universidade de Sao Paulo, Sao Paulo, SP, BrazilCorrespondence: Roseli Gedanke ShavittInstituto de Psiquiatria – HC-FMUSP, R. Dr Ovidio Pires de Campos 785 3o Andar Ala Norte, São Paulo, SP CEP 05403-000, BrazilEmail roseligshavitt@gmail.comAbstract: Transcranial direct current stimulation (tDCS) is a non-invasive neuromodulation technique that has been increasingly examined as an alternative treatment modality for Obsessive-Compulsive Disorder (OCD), due to its low costs, ease of use, and portability. Previous studies have suggested that tDCS may achieve a reasonably good response and present a safe tolerability profile. However, at this point there is not strong evidence for the use of this modality of treatment. Considering that OCD is very heterogeneous with regard to clinical presentation, clinical severity and comorbidities, we have conducted a systematic review of studies on tDCS for OCD aiming to evaluate the clinical characteristics of the selected patients and to discuss perspectives for future studies. A literature search was conducted from inception until March 2019 at PubMed/MedLine and Scielo using the following keywords: “tdcs” or “transcranial direct current stimulation” and “obsessive compulsive disorder”. Out of 45 manuscripts, twelve were included. Most of the included studies are uncontrolled. A few controlled studies reported improvement of OCD, but some limitations need to be considered. Our main findings were that the selected patients were adults with severe OCD and psychiatric comorbidities, medicated at the time of assessment and resistant to at least one previous conventional treatment. We could not find any studies including specific populations such as adolescents, elderly, pregnant and breastfeeding participants. Similarly, the potential use of tDCS has not been tested in patients with less severe OCD, as a first treatment option, or for those who do not tolerate pharmacological treatments. These opportunities should be explored in future controlled trials.Keywords: obsessive-compulsive disorder, transcranial direct current stimulation, neuromodulation